OPTIMIZATION OF SHOE LAST FLATTENING METHODS: COMPARATIVE ANALYSIS OF CAD SYSTEMS FOR 3D TO 2D TRANSFORMATION - CHERTENKO, LILIIA; KAPTIUROVA, DARIIA; BONDAR, OLEXANDER; UDOVENKO, OLEXANDER (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The increasing integration of digital technologies into footwear design has significantly enhanced the accuracy, flexibility, and efficiency of the modeling process for footwear and its components. This study explores the application of methods for designing complex 3D forms of shoe lasts, with a particular focus on converting 3D surfaces into 2D cutting patterns. This stage remains one of the most technically demanding, as it is often associated with considerable deviations and inaccuracies in the resulting data. Special attention is devoted to the challenges of unfolding complex, curved 3D surfaces typical for anatomical footwear lasts. A comparative analysis of the outcomes of flattening 3D last surfaces into 2D layouts was performed using various CAD systems, including Rhinoceros, ShoeMaker, PowerShape, ICAD, MindCAD, and Rhino+Grasshopper. The aim was to evaluate and compare the surface unfolding algorithms implemented in each system. Statistical analysis, particularly ANOVA, was applied to determine significant differences in accuracy among the tested systems. Additionally, optimization of the unfolding process using the Grasshopper plugin showed promising improvements in accuracy and reliability.  The findings emphasize the critical role of selecting the appropriate CAD system in ensuring high-quality footwear design and reducing the need for time-consuming manual corrections. Furthermore, the study revealed that even general-purpose CAD platforms, when configured with suitable parameters, can deliver the precision required for industrial-scale production. This outcome opens further prospects for the digital standardization of processes in the footwear industry, contributing to greater consistency, efficiency, and scalability in product development workflows.
Keywords: 3D-modeling; footwear last; shoe last flattening; CAD-systems